Konsep dan Sistem Pendidikan Islam - Rosyadi, Abdu Rahmat (Ta’dibuna: Jurnal Pendidikan Islam, 2018)
Definition of curriculum of education (manhaj al-dirasah) in Tarbiyah Dictionary is a set of planning tools and media that used by educational institutions in achieving education goals. Curriculum making in lslamic education principles must citated lo education goals. Ingredients of Subjects that programmed by educators should support education goals and not the other way, the goals of education followed subject ingredients.